The present state and future prospects of selected business libraries in the Greater Manila Area a survey - Solivar, Victoria O. (Institute of Library Science, University of the Philippines Diliman, 1975)
This is a study of ten company libraries located in the Greater Manila Area. They were selected from 26 companies which have libraries and which belong to the top 500 corporations of the Philippines for 1973. Profiles of these ten libraries and which belong to the top 500 corporations of the Philippines for 1973. Profiles of these ten libraries are given. Included in the profile are a short history of the library, its objectives, position in the organization structure, personnel, budget, layout, equipment, and a summary of major library activities.